2012
DOI: 10.1073/pnas.1207854109
|View full text |Cite
|
Sign up to set email alerts
|

Bisphenol A alters early oogenesis and follicle formation in the fetal ovary of the rhesus monkey

Abstract: Widespread use of the endocrine disrupting chemical bisphenol A (BPA) in consumer products has resulted in nearly continuous human exposure. In rodents, low-dose exposures have been reported to adversely affect two distinct stages of oogenesis in the developing ovary: the events of prophase at the onset of meiosis in the fetal ovary and the formation of follicles in the perinatal ovary. Because these effects could influence the reproductive longevity and success of the exposed individual, we conducted studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
132
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 189 publications
(145 citation statements)
references
References 44 publications
13
132
0
Order By: Relevance
“…They showed that the set of genes that is downregulated with the BPA/high-sugar diet displays a substantial increase in the number of genes highly expressed in testis ( Figure 4B and Table S2; P = 1.05e-13, Fisher's exact test). These results are in agreement with the observation that BPA impairs germline tissues (Allard and Colaiacovo 2010;Lawson et al 2011;Hunt et al 2012) and suggest that excess sugar might contribute to these toxic effects.…”
Section: Resultssupporting
confidence: 82%
See 4 more Smart Citations
“…They showed that the set of genes that is downregulated with the BPA/high-sugar diet displays a substantial increase in the number of genes highly expressed in testis ( Figure 4B and Table S2; P = 1.05e-13, Fisher's exact test). These results are in agreement with the observation that BPA impairs germline tissues (Allard and Colaiacovo 2010;Lawson et al 2011;Hunt et al 2012) and suggest that excess sugar might contribute to these toxic effects.…”
Section: Resultssupporting
confidence: 82%
“…The effects of BPA exposure on the impairment of chromosome synapsis and double-strand DNA break repair have previously been observed during Caenorhabditis elegans oogenesis (Allard and Colaiacovo 2010), and similar observations were noted in rhesus monkey females (Hunt et al 2012). Hunt et al (2012) further observed abnormal centromere associations, although the mechanisms have remained unclear.…”
Section: Widespread Consequences Of Disrupting the Ribosomal Machinerysupporting
confidence: 59%
See 3 more Smart Citations